2005
DOI: 10.1007/s10800-005-1400-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrolytic oxidation of organic species at mesoporous tungsten trioxide film electrodes under visible light illumination

Abstract: Operation of a photoelectrolyser fitted with a semitransparent semiconducting WO 3 film photoanode is described. Due to its band-gap energy of 2.5 eV, the photoresponse of the WO 3 electrode extends into the blue part of the visible spectrum up to 500 nm. The WO 3 photoanode exhibits particularly high incident photon-to-current efficiencies for the oxidation of several organic species with the maximum occurring at ca. 400 nm. Experiments conducted under simulated AM 1.5 solar illumination demonstrated efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 19 publications
3
51
0
1
Order By: Relevance
“…Questions regarding the electron transport through the porous structure [21] and the photooxidation of water [21,22] or methanol and other small organic molecules have been addressed. [18,22,23] It is remarkable that in all cases a very high conversion efficiency was found. Recently, the oxidation of 2-naphthol on sol-gel WO 3 nanostructured thin-film electrodes was studied, [24] a high photoelectrocatalytic activity again being reported.…”
Section: Introductionmentioning
confidence: 85%
“…Questions regarding the electron transport through the porous structure [21] and the photooxidation of water [21,22] or methanol and other small organic molecules have been addressed. [18,22,23] It is remarkable that in all cases a very high conversion efficiency was found. Recently, the oxidation of 2-naphthol on sol-gel WO 3 nanostructured thin-film electrodes was studied, [24] a high photoelectrocatalytic activity again being reported.…”
Section: Introductionmentioning
confidence: 85%
“…Our recent studies also showed that an increase of the current intensities was also seen when the ink suspension was prepared using CNTs that had already been modified with PDDA and [P 2 W 17 VO 62 ] 8− . It is reasonable to expect that current increases were caused by so-called current doubling historically observed in the presence of different organic molecules [58,59]. As the observed effect led to the pseudocapacitance increase, the ink suspension was prepared as a rule with addition of diethyl ether.…”
Section: Resultsmentioning
confidence: 99%
“…The production of S2O8 2− at pH 2 is approximately six times that at pH 3. Prior to the peroxydisulfate (S2O8 2− ), the photogenerated SO4 − • can initially be formed as intermediates in the WO3 photoanode [42,48]. Subsequently, the generated SO4 − • can directly react with MO in Na2SO4 solution and revert to SO4 2− (Equations (8) and (9)).…”
Section: The Pec Degradation Mechanism Of Momentioning
confidence: 99%